PENGARUH LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PERINGKAT OBLIGASI PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Hailatul Fikriyah (Universitas Pamulang, 2018)
Bond rating is one of the most important indicator about a company’s credit quality. The objective of this research is to know how the liquidity, profitability,and size could influence to the bonds rating. This research use listed on Bursa Efek Indonesia. The samples of this research consist of 15 banks are listed in PT Pefindo from 2009-2012. Research method that used is descriptive analysis, with searching data through library, Financial statement from Bursa Efek Indonesia, and ICMD (Indonesian Capital Market Directory). The techniques of the test of the data be processed by using SPSS (Statistical Product and Service Solution) for windows release 20.00. Multinominal Logistic Regression Analysis with link function was used to the test the hypothesis. Therefore, the conclusion of this research has shown that the variable of liquidity and profitability, not significantly influence the bond rating. Meanwhile variable size significantly influence the bond rating